2020
DOI: 10.1038/s41415-020-1993-9
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating sustainability into assessment of oral health interventions

Abstract: Incorporating sustainability into assessment of oral health interventions Abstract word count: 94 Word count (excl abstract, acknowledgements, references, tables): 2,436 Total number of figures: 3 Total number of tables: 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…A previous LCA study of hypothetical toothbrush designs found that toothbrush handles made from recycled polypropylene toothbrush handles are the most sustainable toothbrush model; however, at the time of conducting this study, a product that follows this model is not currently available on the UK market and plastic recycling in reality is rarely as efficient as it could be. 17 However, with demand for 'eco-friendly' products, toothbrush manufacturers are constantly bringing new products to market, including products that use recycled plastic. The assumption in this study was that the toothbrush is thrown in normal waste.…”
Section: Discussionmentioning
confidence: 99%
“…A previous LCA study of hypothetical toothbrush designs found that toothbrush handles made from recycled polypropylene toothbrush handles are the most sustainable toothbrush model; however, at the time of conducting this study, a product that follows this model is not currently available on the UK market and plastic recycling in reality is rarely as efficient as it could be. 17 However, with demand for 'eco-friendly' products, toothbrush manufacturers are constantly bringing new products to market, including products that use recycled plastic. The assumption in this study was that the toothbrush is thrown in normal waste.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on toothbrushes found that although bamboo toothbrushes have a lower climate change impact compared to plastic toothbrushes, recycled plastic toothbrushes are even better. [Duane et al, 2020] As the popularity of bamboo products increases, the environmental impact of producing bamboo may worsen, feed global demand for this material.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunity for the dental team to reduce patient and staff travel can be achieved by; combining appointments, i.e., family appointments, multiple procedures in one visit, scheduling dental examination by risk assessment approach, employing technology for communication and professional interactions, i.e., teledentistry, encouraging active travel, i.e., cycling and walking, using public transport, car-sharing and electric vehicles by providing electric charging point at the dental practice 11,13 .…”
Section: Domentioning
confidence: 99%